Mental and motor development of Peruvian children treated for severe malnutrition - Pollit, Ernesto; Granoff, Dan (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Twenty-seven children from the slums of Lima, Peru hospitalized and treated for severe protein-calorie malnutrition were given the Bayley Infant Scale of Mental Development and the Bayley Infant Scale of Motor Development. They ranged in age front eleven to thirty-two months with a mean age of 19.5 months. Only two of the children obtained scores above the basal levels of the Scales, thus indicating severe mental and motor retardation despite their apparent somatic recovery from starvation. There was, however, a degree of motor improvement relative to the duration of hospitalization. Eight sibling controls from the slums scored with the normal range for their age, according to the American standardization of Scales.